Tafsir and Gender Normativity in the Digital Age: A Critical Discourse Analysis of Career Women in Instagram Memes - Fadia, Feby Audina; Nugraha Andri Afriza (Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
The increasing use of social media, particularly Instagram, has encouraged new forms of religious expression, including interpretive memes that discuss various social issues. This article critically examines the discourse on career women as articulated in five meme-based posts on the @akhiukhtiantiselfie account. The five posts contain quotations from the Qur’an, hadith, references from several websites, and opinions from religious figures. This study uses a qualitative method with a Critical Discourse Analysis (CDA) framework from Teun A. van Dijk. The results of the study show that, from a textual perspective, the discourse on career women in the interpretive memes of this account is shaped through a textualist approach of interpretation. From a social cognition perspective, the account owner views the phenomenon of career women on social media as a profession that is contrary to Islamic law. Meanwhile, from a social context perspective, the account owner's activities reflect an effort to raise public awareness about the dangers of the phenomenon of career women that is prevalent on various social media platforms. For the owner of the @akhiukhtiantiselfie account, the ideal role for women is in the domestic sphere; therefore, becoming a beauty vlogger or model promoting beauty products is considered unacceptable. However, they still allow women to work outside the home or engage in online commerce, provided certain strict conditions are met. Ultimately, this discourse construction aligns with Salafi’s interpretive patterns, as reflected in the authoritative references and theological arguments employed.